End users' resistance behaviour paradigm in pre-deployment stage of ERP systems: evidence from Bangladeshi manufacturing industry. Issue 5 (3rd May 2021) - Alzahrani, Ahmed; Mahmud, Imran; Thurasamy, Ramayah; Alfarraj, Osama; Alwadain, Ayed
Abstract : Purpose: This study proposes a research model to identify the relevant constructs of employee resistance and symbolic adoption in pre-implementation stage of enterprise resource planning systems in manufacturing industries, drawing suitable support from the existing body of literature. The proposed model is a combination of the status quo bias theory and absorptive capacity theory to measure employee resistance that negatively lead to symbolic adoption of a user. Design/methodology/approach: This research used a self-administered questionnaire to survey 221 participants from five organizations in the manufacturing industry, all working towards deploying enterprise resource planning (ERP) systems. Findings: The results show that factors contributing to status quo bias and absorptive capacity impact end-user grumbling. Furthermore, end-user grumbling affects symbolic adoption substantially. Practical implications: This study provides researchers, practitioners and ERP vendors a broader overview of employees' resistance and motivation for using newly deployed systems. Originality/value: In the past two decades, both practitioners and academicians are investigating the technical and non-technical features that assist end-users to adopt the system. Information system theories center on the post-deployment stage, with rare attempts to identify users' resistance and mental willingness to accept technology in the pre-adoption phase, which is very crucial for the success of ERP.